2015
DOI: 10.1096/fj.14-265066
|View full text |Cite
|
Sign up to set email alerts
|

Direct or indirect stimulation of adenosine A 2A receptors enhances bone regeneration as well as bone morphogenetic protein‐2

Abstract: Promoting bone regeneration and repair of bone defects is a need that has not been well met to date. We have previously found that adenosine, acting via A 2A receptors (A2AR) promotes wound healing and inhibits inflammatory osteolysis and hypothesized that A2AR might be a novel target to promote bone regeneration. Therefore, we determined whether direct A2AR stimulation or increasing endogenous adenosine concentrations via purine transport blockade with dipyridamole regulates bone formation. We determined whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 55 publications
6
101
1
2
Order By: Relevance
“…The work presented here showed no effects of adenosine, 2-chloroadenosine, GR79236 or BAY606583 on calvarialderived osteoblasts; this is in broad agreement with previous studies which showed exogenous adenosine had no effect on cultured rat osteoblasts [11,29]. However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The work presented here showed no effects of adenosine, 2-chloroadenosine, GR79236 or BAY606583 on calvarialderived osteoblasts; this is in broad agreement with previous studies which showed exogenous adenosine had no effect on cultured rat osteoblasts [11,29]. However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a synthetic A 2B receptor agonist has been shown to increase bone formation, and bone marrow osteoblasts from A 2B receptor knockout mice display reduced levels of bone formation [30]. Recently, it has also been reported that stimulation of the A 2A receptors can enhance bone regeneration [31].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies A2AR stimulation has been shown to diminish inflammatory osteolysis and increase osteoblast numbers in inflamed bone [55]. In the context of a bone defect, A2AR helps restore bone homeostasis by increasing osteoblasts while decreasing osteoclast number and activity [77]. Yet, He et al observed no effect on human osteoblast differentiation and mineralization with activation or downregulation of the A2AR [78].…”
Section: P1 Receptors: A2armentioning
confidence: 95%
“…Mediero et al observed enhanced bone regeneration, and an increase in bone volume and osteoblast expression of markers for bone formation including osteocalcin and osteonectin in mouse calvaria treated with either an A2AR agonist (CGS21680) or dipyridamole which blocks adenosine uptake. In addition, osteoclast markers were decreased in vitro and osteoclast numbers were reduced in vivo [77]. Adenosine receptor agonists or agents that increase local adenosine concentration may be preferred approaches to inducing bone regeneration following orthopedic surgeries compared to the currently used recombinant bone morphogenetic proteins, which are known to inflame nearby tissues, stimulate aberrant bone formation and carry higher complication rates [79].…”
Section: P1 Receptors: A2armentioning
confidence: 99%
See 1 more Smart Citation